Eingeordnete Freiheit : Freiheit und Vorsehung bei Origenes - Benjamins, H. S. (Vigiliae Christianae, Supplements, 1994)
Eingeordnete Freiheit compares Origen's notion of freedom of choice with the concepts of contemporary philosophers. The first chapter deals with the philosophical problem of freedom of choice throughout the history of Greek philosophy. In the second chapter Origen's writing on this topic is assembled, translated, analyzed and commented upon. The comparison between Origen and his contemporaries leads in chapter three to the conclusion that Origen's concept of freedom differs especially from the philosophical perspective, since human freedom does not stand in opposition to the inevitable pattern of the pronoia or heimarmene but to Gods care for every individual. Chapter four shows that the notion of oikonomia in Christian theology is based on the concept of providence in Origen.